A rare cutaneous adverse effect secondary to cabozantinib therapy. Issue 12 (26th November 2018) - Growcott, Siona; Banner, Alexandra; Bray, Adam; Hilman, Serena
Abstract: Cabozantinib is a tyrosine kinase inhibitor which is increasingly being used for the treatment of metastatic renal cell cancer. Skin toxicity such as palmar-plantar erythrodysesthesia is not uncommon with such agents. However, bullous skin reactions are not common and we report the case of a patient with metastatic renal cell cancer who experienced such cutaneous toxicity.